Acceptor-induced cooperative supramolecular co-assembly with emissive charge-transfer for advanced supramolecular encryption. Issue 64 (14th July 2020) - Gao, Zhao; Yan, Fei; Qiu, Shuai; Han, Yifei; Wang, Feng; Tian, Wei
Abstract : A novel acceptor-induced cooperative supramolecular co-assembly based on a dendritic electron donor and 1, 2, 4, 5-tetracyanobenzene acceptor has been successfully developed. Abstract : A novel acceptor-induced cooperative supramolecular co-assembly based on a dendritic electron donor and 1, 2, 4, 5-tetracyanobenzene acceptor has been successfully developed. The resulting co-assembly is capable of displaying emissive charge transfer properties and intriguing vapo-fluorochromic behaviors, which can be used for supramolecular encryption applications with reversible authentication.